Farm management capacities contribute to sustainability of rural livelihoods amongst small farmers in district Layyah, Punjab, Pakistan - Abbas, Rizwan; Mirza, Faria Ibad; Afzal, Aneela (Journal of Pure and Applied Agriculture, 2023)
This study reveals that about 98% of the respondents had farms, while 100% respondents had livestock assets for their livelihoods in district Layyah, Punjab, Pakistan. The study will help in the development of relevant sustainability policies. ABSTRACT Punjab is one of the fertile provinces of Pakistan but poverty is prevailing especially in its rural areas. The main reasons for poverty in these areas include the lack of planning as well as implementation of policies. The present study was conducted in district Layyah, Punjab to investigate the sustainability of rural livelihoods among the small farmers. The results show that a majority of the respondents (68.33%) had their own land and 98 percent of the respondents had a farm. 41.66% were farming on the current farm for a period of 11-15 years. During this study, it was found that 87% respondents had electricity available for farming activities and 74.33 percent of respondents were using canal water to irrigate their land. A majority of the respondents (37.66%) were holding 1.1-2 ha of land and performing cultivation activities. As far as active membership of a community organization is concerned, about two thirds (65%) of the respondents held active membership in a community organization via different non-government organizations. After taking into account livestock and farming; 100 percent respondents told that they possessed these assets as their primary financial capital because the area was rural in nature and the targeted respondents were farmers by occupation. Agriculture loans were also found to be a source of income for a majority (61.66%) of the respondents. The findings of this study will be helpful for policy makers to develop policies that correspond to the realities of farming in the region.